2011
DOI: 10.1007/s10008-011-1591-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and electrocatalytic performance of Fe–N–C for electroreduction of H2O2

Abstract: Fe-N-C catalysts were prepared through metal-assisted polymerization method. Effects of carbon treatment, Fe loading, nitrogen source, and calcination temperature on the catalytic performance of the Fe-N-C for H 2 O 2 electroreduction were measured by voltammetry and chronoamperometry. The Fe-N-C catalyst shows optimal performance when prepared with pretreated active carbon, 0.2 wt.% Fe, paranitroaniline (4-NA) and one-time calcination. The Fe-N-C catalyst displayed good performance and stability for electrore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It can be observed that there were small bubbles formed on the electrode surface when H 2 O 2 concentration is higher than 0.6 mol L −1 . The comparation of H 2 O 2 catalytic performance on NiCo 2 O 4 /Ni foam with other representative nanomaterials reported previously 16, 20, 21, 47–50 was shown in Table 1. The current density is chosen at –0.4 V from the CV measurement.…”
Section: Resultsmentioning
confidence: 80%
“…It can be observed that there were small bubbles formed on the electrode surface when H 2 O 2 concentration is higher than 0.6 mol L −1 . The comparation of H 2 O 2 catalytic performance on NiCo 2 O 4 /Ni foam with other representative nanomaterials reported previously 16, 20, 21, 47–50 was shown in Table 1. The current density is chosen at –0.4 V from the CV measurement.…”
Section: Resultsmentioning
confidence: 80%
“…Not only active but also selective cathodes for two-electron reduction of H2O2 should be developed to achieve high power fuel cells using H2O2 as an oxidant. Suitable catalysts for two-electron reduction of H2O2 would be found in electrodes used in H2O2 detection sensors but not used in fuel cells, such as shape-controlled metal nanoparticles, 79,80 graphene based materials, [81][82][83] polyoxometalate, [84][85][86][87][88] and metal complexes. 89,90…”
Section: Resultsmentioning
confidence: 99%